A general strategy for the fabrication of high performance microsupercapacitors. (September 2015) - Kurra, Narendra; Jiang, Qiu; Alshareef, H.N.
Abstract: We propose a generic strategy for microsupercapacitor fabrication that integrates layers of reduced graphene oxide (rGO) and pseudocapacitive materials to create electrode heterostructures with significantly improved cycling stability and performance. Our approach involves a combination of photolithography and a simple transfer method of free-standing reduced graphene oxide film onto an Au/patterned photoresist bilayer. The resulting stack (rGO/Au/patterned resist/substrate) is then used for the electrochemical deposition of various pseudocapacitive materials before the final step of lift-off. To prove the viability of this method, we have successfully fabricated microsupercapacitors (MSCs) with the following interdigitated electrode heterostructures: MnO2 /rGO, Co(OH)2 /rGO and PANI/rGO. These MSCs show better performance and cycling stability compared to the single layer, (i.e., rGO-free) counterparts. The interdigitated electrode heterostructures result in MSCs with energy densities in the range of 3–12 mW h/cm 3 and power densities in the range of 400–1200 mW/cm 3, which is superior to the Li thin film batteries ( E =10 mW h/cm 3 ), carbon, and metal oxide based MSCs ( E =1–6 mW h/cm 3 ) while device energy densities are in the range of 1.3–5.3 mW h/cm 3, corresponding power densities are in the range of 178–533 mW/cm 3 . These results can be explained by a facilitated nucleation model, where surface topology of the rGO film creates a favorable environment for the nucleation and growth of pseudocapacitive materials with strong interfacial contacts and enhanced surface area. This approach opens up a new avenue in fabricating MSCs involving a variety of heterostructures combining electrical double layer carbon type with Faradaic pseudocapacitive materials for enhanced electrochemical performance. Graphical abstract: Micro-pseudocapacitors based on pseudocapacitive/reduced graphene oxide heterostructures have been fabricated which exhibit improved cycling performance with volumetric energy density superior to the current state-of-the-art thin film batteries and carbon, metal oxide based microsupercapacitors. Highlights: A general strategy is proposed to fabricate micro-pseudosupercapacitors with heterostructured electrodes. Combines electrical double layer carbon type with Faradaic pseudocapacitive materials. The improved electrochemical stability is demonstrated. This study provides an insight into the current state-of-the-art micro-pseudocapacitors.